Urban storm flood modeling applied to Barangay Bambang in Pasig City - Manalastas, Guian Carlo D.G.; Castro, Peter Paul M. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
Nowadays, almost all countries, especially the Philippines, has been experiencing flooding problems. One obvious reason is today's rapid urbanization in many parts of the world, which is not always accompanied by a sufficient increase of the drainage system capacity. Furthermore, water knows no political boundaries and seeks its own level depending on the topography of an area. It is common that the natural watershed of an area is not in line with its political boundaries. With this being said, this study addressed the issues presented above by mode II ing a small catchment area based on its political boundaries such as in a barangay scale. The software used in this study is SWMM which is an open and free software developed by the US Environmental Protection Agency (US EPA). In this model, nearby water bodies and other inflows and outflows from nearby areas outside the political boundaries were taken into consideration. This scenario which is what actually happens in real life is modeled to produce more accurate results. However, many difficulties were encountered during the research such as lack of data and difficulties in calibration and validation. Despite percentage errors of -47.05% and -25% in the inundation depths, the parts of the area which were flooded were the same as the identified flood prone areas of the barangay as reported by the Pasig City government. Hence, the simulation results have shown that the model has represented the study area's hydraulic behavior well.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Floods -- Philippines -- Pasig City (Manila); Hydraulic models